THE INFLUENCE OF RELIGIOSITY AND HALAL AWARENESS ON THE PURCHASE INTENTION OF THE MUSLIM Z GENERATION IN WARDAH COSMETIC PRODUCTS (CASE STUDY AT KAZANA COSMETICS STORE) - Adelia Winanda; Ahmad Rafiki; Yuni Syahputri (Jurnal Ekonomi, 2023)
The topic of this study is "The Influence of Religiosity and Halal Awareness on Muslim Generation Z's Purchase Interest in Wardah Cosmetic Products (Case Study at Kazana Cosmetics Shop)." Associative research is the name given to this form of investigation. The research population consisted of 397 clients who purchased Wardah cosmetic goods from Kazana Cosmetics Shop. This approach makes use of "purposeful sampling," which is choosing a sample based on a predefined standard. The Slovin formula determines the number of samples in this example to be 80 persons. The SPSS 26 program was used to examine the study data, which comprised the T test, date determination coefficient, normality test, heteroscedasticity test, multicollinearity test, and multiple linear regression analysis. It can be observed from the t-test that the variables of religiosity and halal awareness have a positive and significant effect on the purchase intention of the Muslim generation z in wardah cosmetic products.